Mobility as a service (MaaS) adoption: Assessing heterogeneity across university communities - Fulvio Silvestri; Valentina Costa; Luca Pastorelli (Transportation Engineering)
This study investigates the willingness to adopt (WTA) Mobility as a Service (MaaS) solutions among members of Italian university communities, based on over 4000 responses collected through two survey campaigns at the Politecnico di Milano and the University of Genoa. Ordered logit models were estimated to assess the influence of socio-demographic characteristics, travel habits, and individual perceptions on MaaS adoption. Identified key determinants include travelers’ satisfaction with current transport options, which is negatively associated with WTA, in line with existing findings that satisfied users are less likely to change travel behavior. Results partially align with prior studies that identify private car ownership as a barrier. Use of journey planning apps is positively associated with MaaS adoption, reinforcing prior research on the importance of digital familiarity. This study also presents findings that diverge from previous literature: age does not significantly influence WTA, and services such as bike sharing and car sharing do not yield measurable utility in the adoption decision. The analysis reveals substantial heterogeneity in preferences both across and within the two university contexts, as confirmed by the significance of several random parameters capturing individual-level variation. These results underscore the importance of developing flexible, context-sensitive MaaS strategies. Given the diversity of preferences and influencing factors, a one-size-fits-all approach is unlikely to be effective.